2015
DOI: 10.1038/ncomms9581
|View full text |Cite
|
Sign up to set email alerts
|

Topological data analysis for discovery in preclinical spinal cord injury and traumatic brain injury

Abstract: Data-driven discovery in complex neurological disorders has potential to extract meaningful syndromic knowledge from large, heterogeneous data sets to enhance potential for precision medicine. Here we describe the application of topological data analysis (TDA) for data-driven discovery in preclinical traumatic brain injury (TBI) and spinal cord injury (SCI) data sets mined from the Visualized Syndromic Information and Outcomes for Neurotrauma-SCI (VISION-SCI) repository. Through direct visualization of inter-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(150 citation statements)
references
References 56 publications
3
139
0
Order By: Relevance
“…The result is a low-dimensional network representation of the data in which nodes represent sets of samples with similar global transcriptional profiles, and edges connect nodes that have at least one sample in common. For our analysis we used 2D Locally Linear Embedding 37 as dimentionality reduction algorithm and variance normalized Euclidean metric 38 as distance. Single-linkage clustering was performed in each of the pre-images of the bins using a previously described algorithm 39 .…”
Section: Methodsmentioning
confidence: 99%
“…The result is a low-dimensional network representation of the data in which nodes represent sets of samples with similar global transcriptional profiles, and edges connect nodes that have at least one sample in common. For our analysis we used 2D Locally Linear Embedding 37 as dimentionality reduction algorithm and variance normalized Euclidean metric 38 as distance. Single-linkage clustering was performed in each of the pre-images of the bins using a previously described algorithm 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in the era of precision medicine, big data-driven discovery in complex trauma situations such as TBI or polytrauma might be feasible through the use of bioinformatics tools such as topological data analysis. Such strategies might improve the phenotyping of injury patterns, precision diagnosing and treatment planning 198 . Here we focused on physical trauma but have neglected complex interactions with the psychological dimension; for example, the innate immune response after psychological trauma reveals in part similarities to the reactions described after physical trauma.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It is possible that the retrospective analysis of anesthetic records in the current study, from data recorded at 5‐minute intervals using predominantly indirect blood pressure recording techniques, meant that the severity and regularity of hypotension were underestimated. A recent study also suggested that acute spikes of systemic hypertension at the time of experimental SCI are associated with poorer outcome in rodent models, suggesting that both extremes of blood pressure might in fact have harmful consequences, and hypertension would have been missed with the current study design 45. The effect of systemic hypotension on outcome in acute SCI has been extensively evaluated in experimental studies and human medicine 21, 26.…”
Section: Discussionmentioning
confidence: 99%